Inadequacies and variations of maternity leave policies throughout the world: special focus on Bangladesh - Anam, Rumana Liza (BRAC University, 2010)
There has been a dramatic increase in the representation of women in the workforce in Bangladesh and throughout the world. However, women face major hurdles in most parts of the world in their advancement in organizations as maternity leave and other benefits such as on site crèche or flextime are still not provided as per requirements. Thus women are falling behind in their careers throughout the world. There are also wide disparities in the benefits women get legally in different parts of the world. This review paper seeks to collect the answers to many questions about maternity leave heretofore largely un-addressed.